Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
EWaS3 2018 2018
DOI: 10.3390/proceedings2110589
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Pipe Failure in Drinking Water Distribution Networks by Comsima

Abstract: Comsima is a mechanical model that calculates stresses and joint rotations in drinking water distribution pipes based upon several loadings on the pipe (soil, traffic, water pressure, differential settlements). Pipe degradation mechanisms (slow crack growth resistance for PVC and calcium leaching for AC) were added to the model. A comparison with failure registration for an area in the Netherlands using satellite data to determine differential settlements shows that pipes with higher stresses or higher joint r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The performance of the proposed technique results demonstrated that the frequency of low-pressure occurrences is significantly marginal whereas a higher minimum pressure criterion would unavoidably augment expected pipe break rates. Wols et al (2018) used a mechanical technique, introduced as Comsima, to compute the break rate with consideration of stresses and joint rotations in a part of WDN in the Netherlands on the basis of quite a few loading conditions on the pipe (i.e., soil, traffic, water pressure, and differential settlements). Robles-Velasco et al…”
Section: Literature Review: Overview Of Existing Techniquesmentioning
confidence: 99%
“…The performance of the proposed technique results demonstrated that the frequency of low-pressure occurrences is significantly marginal whereas a higher minimum pressure criterion would unavoidably augment expected pipe break rates. Wols et al (2018) used a mechanical technique, introduced as Comsima, to compute the break rate with consideration of stresses and joint rotations in a part of WDN in the Netherlands on the basis of quite a few loading conditions on the pipe (i.e., soil, traffic, water pressure, and differential settlements). Robles-Velasco et al…”
Section: Literature Review: Overview Of Existing Techniquesmentioning
confidence: 99%
“…However, the technique unlocks the possibility to study the degradation phenomena that occur in AC in more detail. At the current state of knowledge, homogeneous degradation at a constant rate is typically assumed [17,18]. According to the results presented in Section 3.1, this assumption represents an exception rather than a rule, as inhomogeneous degradation was prevalent at both the inner and the outer pipe wall.…”
Section: Lessons Learned About the Deterioration Of Ac Drinking Water Pipes In Generalmentioning
confidence: 99%
“…In previous work, it was determined that X-ray computed tomography may indeed provide a detailed description of AC pipe degradation [15]. In that work, it was also revealed that the leaching of AC drinking water pipes occurs in a far less homogeneous way than is traditionally assumed [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Presumably, the localized nature of the external degradation in Figures 2 and 3 is related to the corresponding distributions of aggressive soil components around the pipe when the pipes were in use. The inhomogeneous nature of the internal degradation is more remarkable, however, since the leaching of calcium hydroxide from the AC pipes into the drinking water is typically understood to be a diffusion-controlled process that occurs homogeneously across the pipe surface [6]. Nonetheless, the patterns described above were typical for the 32 pipes that were scanned in total.…”
Section: Degradation Patterns Of Acmentioning
confidence: 99%